PENINGKATAN KARAKTER KREATIF DAN MANDIRI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE KELOMPOK INVESTIGASI - Lestari; Malawi, Ibadullah; Sudarmiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this study is that students in group B2 of Tunas Rimba Madiun Kindergarten have not achieved their maximum creative and independent character, character learning is carried out conventionally and through verbal and instructional delivery of values. This study aims to describe and analyze the implementation of the investigation group learning model in improving creative and independent character. This study uses a qualitative approach with the type of Classroom Action Research and is carried out in 2 cycles. Data collection techniques use observation and documents. The results of the study show that students' creative and independent character can be improved through the investigation group learning model. Creative character is at a percentage of 55% and increases to 80% in cycle II. While the independent character in cycle I has a percentage of 58% increasing to 87% in cycle II. Thus, the achievement of completeness is in accordance with the performance indicators reaching 80%. The investigation group learning model can improve creative and independent character in students in group B2 of Tunas Rimba Madiun Kindergarten.